Valorization of the essential oil from Drypetes gossweileri S. Moore (Putranjivaceae): in vitro, in vivo, and in silico nematicidal activity - Mbula, Jean Pierre; Andres, Maria Fe; Kitete, Emmanuel M.; Kasiama, N. G.; Tshilanda, D. D.; Ngbolua, K. N.; Tshibangu, D. S. T.; Onautshu, O.; González-Coloma, Azucena; Mpiana, Pius T. (Frontiers in Plant Science, 2023)
The chemical composition, insect antifeedant, in vtro/in vivo nematicidal activity, phytotoxicity, and in silico nematicidal activity of the essential oil (EO) of the African medicinal plant Drypetes gossweileri were studied. Chemical analysis using GC/MS indicated that benzyl isothiocyanate (96.23%) was the major compound, followed by benzyl cyanide (1.38%). The biocidal effects of this oil were tested against insect pests and root-knot nematodes. All the insect species tested were significantly affected by the oil according to their feeding adaptations (Spodoptera littoralis and Myzus persicae were less affected than Rhopalosiphum padi) with efficient doses (EC50) of 29.4 8.3 μg/cm2, 14.744 8.3 μg/cm2, and 8.3 μg/cm2, respectively. The oil was highly effective against juveniles J2 of the nematode Meloidogyne javanica, with LC50–LC90 values of 0.007 mg/mL–0.0113 mg/mL. D. gossweileri EO at minimum lethal concentrations (MLC) and below strongly inhibited egg hatching in vitro, whereas soil treatment caused a strong suppression of nematode population, infection frequency, and multiplication rate. The EO inhibited ryegrass (Lolium perenne) germination at 0.4 mg/mL, while at 0.1 mg/mL, its effects on germination, root and leaf growth were moderate (32.4%, 8.4%, and 18.3%, respectively). The tomato (Solanum lycopersicum) germination was not affected by the EO, but the root growth was reduced (56% at 0.1 mg/mL) at a dose 10 times higher than the LD50 calculated for M. javanica J2 mortality. Molecular docking of the nematicidal effects of the oil using PyRx revealed a strong interaction between potassium chloride transporting KCC3 (PDB ID: 7D90) and benzyl cyanide at a distance of 2.20 A° with GLN C:350, followed by benzyl isothiocyanate at a distance of 2.78 A° with ARG B:294. The in vivo nematicidal effects of D. gossweileri EO on M. javanica penetration and reproduction in tomato roots further support the potential of this EO as a nematicidal agent with insect antifeedant effects, which could be used by local farmers for crop protection.